A Comment on "Se Habla Espa\~nol: Spanish-Language Appeals and Candidate Evaluations in the United States" - Efrén Cruz Cortés; John Lee; Emilio Lehoucq; Vsevolod Suschevskiy (Institute for Replication (I4R), 2024)
Zárate, Quezada-Llanes, and Armenta (2024) examine whether Hispanic and Anglo voters change voting behavior if a political candidate speaks to them in Spanish and whether it matters how proficient in Spanish the candidate sounds. They find that Hispanic support for the Anglo and Hispanic candidates is higher in the native-like Spanish condition compared with the English-only condition. Relative to the English condition, non-native Spanish does not increase support for the Anglo candidate, but it decreases support for the Hispanic candidate. They find mixed effects for the Anglo participants. We conducted computational and robustness reproductions. First, we successfully computationally reproduced all the main results. Second, we constrained the analysis to participants that passed the manipulation checks (this was not done by the authors). We find the same results hold. Notice we constrained ourselves to study 1, which is based on data by Prolific.
Keywords: 330